PENGARUH PENGALAMAN KERJA AUDITOR, AKUNTABILITAS DAN PROFESIONALISME TERHADAP KUALITAS AUDIT (STUDI EMPIRIS PADA KANTOR AKUNTAN PUBLIK DI WILAYAH KOTA BEKASI DAN DKI JAKARTA) - Nilasari, Sekar; Maidani, Maidani; Eprianto, Idel (LPPM Institut Pendidikan Nusantara Global, 2024)
This research was conducted with the aim of measuring the influence of auditor work experience, accountability and professionalism on audit quality. The samples used in this research were auditors who worked at 5 public accounting firms in the Bekasi City area and 5 public accounting firms in the DKI Jakarta area. The number of respondents in this study was 100 respondents. The sampling technique used in this research was purposive sampling. The data collection method used in this research is a questionnaire method. The questionnaire was processed using SPPS version 26. The results of this study show that the auditor's work experience has no effect on audit quality, accountability has a positive effect on audit quality, professionalism has a positive effect on audit quality.